2021
DOI: 10.3354/aei00399
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel ADP-ribosylation factor gene from Macrobrachium nipponense and its response to ammonia nitrogen stress

Abstract: ADP-ribosylation factors (Arfs) are guanosine triphosphate (GTP)-binding proteins that play essential roles in membrane trafficking, and they have been recently reported to be involved in innate immunity in crustaceans. However, little information is available on Arfs in the oriental river prawn Macrobrachium nipponense and their response to ammonia nitrogen stress. In this study, we identified a novel M. nipponense Arfn gene (MnArfn). The full-length cDNA of MnArfn was 1076 bp. It contained a 537 bp open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Ammonia nitrogen poses a serious threat to various aquatic organisms, including fish, shellfish, and aquatic plants [32][33][34][35][36][37]. The digestive tract plays a crucial role in the transmission and entry of pathogens, making it highly susceptible to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia nitrogen poses a serious threat to various aquatic organisms, including fish, shellfish, and aquatic plants [32][33][34][35][36][37]. The digestive tract plays a crucial role in the transmission and entry of pathogens, making it highly susceptible to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, biological filtration and water exchange are expensive processes, thus limited for many prawn farmers (Ren & Pan, 2014; Sinha et al, 2013). Currently, research is also focused on cultivating new varieties of M. nipponense that are resistant to ammonia stress (Guo et al, 2021; Sun, Luo, et al, 2019; Sun, Wu, et al, 2019; Yu et al 2019). However, developing new strains for aquaculture is time consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia is a common stressor in intensive culture systems as the main nitrogenous waste excreted by crustaceans 4,25 . To date, the acute toxicity of ammonia on oriental river prawn on immune response and oxidative stress have been reported 4,26,27 . The studies identified the immunity genes for combating ammonia stress and biomarkers for ammonia exposure in oriental river prawn 4,26,28 .…”
Section: Introductionmentioning
confidence: 99%
“…4,25 To date, the acute toxicity of ammonia on oriental river prawn on immune response and oxidative stress have been reported. 4,26,27 The studies identified the immunity genes for combating ammonia stress and biomarkers for ammonia exposure in oriental river prawn. 4,26,28 However, studies on the chronic toxic effects of ammonia on oriental river prawn are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation